ONLINE TEACHING IN MATHEMATICS AND NATURAL SCIENCES FACULTY, UNIVERSITAS NEGERI SURABAYA IN EARLY PANDEMIC OF COVID-19: PREPARATION, IMPLEMENTATION, AND ASSESSMENT - Wahyu Budi Sabtiawan; Elok Suidibyo; Bertha Yonata; Nugrahani Primary Putri; Guntur Trimulyono; Dian Savitri (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2020)
The study aims to evaluate teaching in Mathematics and Natural Sciences Faculty of Universitas Negeri Surabaya during early pandemic of Covid-19. The evaluation was based on three aspects, that were, preparation of teaching, implementation of teaching, and assessment conducted by lectures. The design of the study was evaluation research adapted from Kirkpatrick Evaluation Design and focused on learning processes. The study evaluated 26 lectures through observation in each class. There were findings that 98% of teaching preparations met criteria. Also, implementation of teaching aspect got good score, that was, 97%. On the other hand, the lectures were scored in lower percentage for assessment aspect compared to the other two aspects. The aspect got 87%. The study found that 13% of lectures was lack of feedback.Keywords: Online teaching, Universitas Negeri Surabaya, Pandemic of Covid-19